Gallium(III) chelates of mixed phosphonate-carboxylate triazamacrocyclic ligands relevant to nuclear medicine: structural, stability and in vivo studies - Prata, Maria I. M. (2017)
Three triaza macrocyclic ligands, H6NOTP (1,4,7-triazacyclononane-N,N′,N″-trimethylene phosphonic acid), H4NO2AP (1,4,7-triazacyclononane-N-methylenephosphonic acid-N′,N″-dimethylenecarboxylic acid), and H5NOA2P (1,4,7-triazacyclononane-N,N′-bis(methylenephosphonic acid)-N″-methylene carboxylic acid), and their gallium(III) chelates were studied in view of their potential interest as scintigraphic and PET (Positron Emission Tomography) imaging agents. A 1H, 31P and 71Ga multinuclear NMR study gave an insight on the structure, internal dynamics and stability of the chelates in aqueous solution. In particular, the analysis of 71Ga NMR spectra gave information on the symmetry of the Ga3+ coordination sphere and the stability of the chelates towards hydrolysis. The 31P NMR spectra afforded information on the protonation of the non-coordinated oxygen atoms from the pendant phosphonate groups and on the number of species in solution. The 1H NMR spectra allowed the analysis of the structure and the number of species in solution. 31P and 1H NMR titrations combined with potentiometry afforded the measurement of the protonation constants (log KHi) and the microscopic protonation scheme of the triaza macrocyclic ligands. The remarkably high thermodynamic stability constant (log KGaL =34.44 (0.04) and stepwise protonation constants of Ga (NOA2P)2− were determined by potentiometry and 69Ga and 31P NMR titrations. Biodistribution and gamma imaging studies have been performed on Wistar rats using the radiolabeled 67Ga(NO2AP)− and 67Ga (NOA2P)2−chelates, having both demonstrated to have renal excretion. The correlation of the molecular properties of the chelates with their pharmacokinetic properties has been analysed.